Restoring autophagic flux attenuates cochlear spiral ganglion neuron degeneration by promoting TFEB nuclear translocation via inhibiting MTOR. Issue 6 (3rd June 2019) - Ye, Bin; Wang, Quan; Hu, Haixia; Shen, Yilin; Fan, Cui; Chen, Penghui; Ma, Yan; Wu, Hao; Xiang, Mingliang
ABSTRACT: Macroautophagy/autophagy dysfunction is associated with many neurodegenerative diseases. TFEB (transcription factor EB), an important molecule that regulates lysosomal and autophagy function, is regarded as a potential target for treating some neurodegenerative diseases. However, the relationship between autophagy dysfunction and spiral ganglion neuron (SGN) degeneration and the role of TFEB in SGN degeneration has not yet been established. Here, we showed that in degenerated SGNs, induced by sensory epithelial cell loss in the cochlea of mice following kanamycin and furosemide administration, the lipofuscin area and oxidative stress level were increased, the nuclear-to-cytoplasmic TFEB ratio was decreased, and the late stage of autophagic flux was impaired. After autophagy dysfunction was partially ameliorated with an MTOR inhibitor, which promoted TFEB translocation into the nucleus from the cytoplasm, we found that the lysosomal deficits were significantly relieved, the oxidative stress level was reduced, and the density of surviving SGNs and auditory nerve fibers was increased. The results in the present study reveal that autophagy dysfunction is an important component of SGN degeneration, and TFEB may be a potential target for attenuating SGN degeneration following sensory epithelial cell loss in the cochlea of mice. Abbreviations : 3-NT: 3-nitrotyrosine; 4-HNE: 4-hydroxynonenal; 8-OHdG: 8-hydroxy-2ʹ-deoxyguanosine; ABR: auditory brainstem response; APP: amyloid beta (A4) precursor protein; CLEAR: coordinated lysosomal expression and regulation; CTSB: cathespin B; CTSD: cathespin D; SAMR1: senescence-accelerated mouse/resistance 1; SAMP8: senescence-accelerated mouse/prone 8; MAPK1/ERK2: mitogen-activated protein kinase 1; MTOR: mechanistic target of rapamycin kinase; SGN: spiral ganglion neuron; SQSTM1/p62: sequestosome 1; TEM: transmission electron microscope; TFEB: transcription factor EB